Movie Making as Critical Pedagogy Conscientization through Visual Storytelling - Walker, Grady (Palgrave Studies in Communication for Social Change, 2018)
Can the stories people tell influence the way they see the world? This book seeks to address that question through a study of the viability of movie making as a critical pedagogy activity. Positioned at the intersection of education and communication for social change, it explores the relationship between the generation of subjective knowledge through storytelling and analysis, and systemic change. Central to the book is a case study from Nepal. By using video as the action element and analytical material of coursework, youth participants generated a new critical awareness, engendered by themes arising from group discussion. Through the analysis of these themes participants initiated an emergence known as conscientization. Led by two critical educators, participants used the production, screening, and analysis of their own movies to propel the course, or praxis, forward. This book seeks to inform the practice of critical pedagogy both practically and theoretically, and also offers a contribution to the fields of participatory action-research and communication for social change.